Social Representations of Women Managers in Private Banking Industry - Minibas-Poussard, Jale; Seçkin-Çelik, Tutku; Bingöl, Haluk Baran; Ak Akyol, Feyza; Erkmen, Turhan (International Journal of Contemporary Economics and Administrative Sciences, 2023)
Women’s presence in managerial positions in banking industry has grown globally, although men still seem to dominate these positions in Turkey. This article investigates the way and extent to which the social representations of women managers in private banking industry in Turkey has evolved recently. We compare and contrast representations of men and women in two periods: 2008 (N=220) and 2018 (N=172), by observing the changes and evolutions/transformations that occurred over a decade. Besides the positive representations observed for women managers among male and female participants similar to previous studies, negative representations were also discovered with contrasts among men and women. An important highlight of the study was the increased number of negative representationsassociated with women managers by women participants between 2008 and 2018. This study has important practical implications about women managers’ training.